Green Building Strategy of University Campuses in Cold Regions: A Case Study of Xi 'an - Wu, Xiaoran (Transactions on Engineering and Technology Research, 2024)
Building as a major body of carbon emission and energy consumption, how to reduce energy consumption needs to be solved. As a large building type that is closely related to people's lives, it is important to find green solutions according to local conditions. This paper explores the green building strategies of university campuses in cold regions by combining building climate zoning, especially taking Xi 'an as an example. By constructing and analyzing the green building simulation model, based on the basic model, the analysis method of control variables and scheme comparison is used to discuss the orientation, building type and envelope material, and evaluate the energy performance and environmental impact of different building schemes. The results show that, in the design of green campus in cold areas, different influencing factors of building energy consumption are selected according to various conditions, reasonable planning is made according to local conditions, and the optimal scheme is obtained by combining comparative experiment simulation or analysis and comparison, so as to obtain optimization strategy research, so as to reduce building energy consumption, realize green building design, and provide reference for green building practice in cold areas in the future. It provides a useful reference for the sustainable development of university campus buildings.